Psilocybin and Motor Function: A Triple‐Blind, Dose‐Finding Study in Healthy Participants - Chiranth Bhagavan; Richard Kanaan; Olivia Carter; Glenn Nielsen; David Berlowitz; Sara Issak; Sabine Braat; Sophie Zaloumis; Zachary Attard; Georgina Oliver; Deanne Mayne; David McKernon; et al. (Psychiatric Research and Clinical Practice)
Background There has been a resurgence of research into the potential therapeutic benefits of psychedelics for neuropsychiatric disorders. Classic psychedelics, such as psilocybin, exert complex effects on higher cognitive functions such as perception and awareness, but their impact on motor function remains unexplored. Moreover, there is a theoretical rationale for using psychedelics to promote motor retraining in certain neuropsychiatric conditions associated with motor dysfunction. This protocol paper outlines the first study to investigate the feasibility and safety of performing movement tasks during the acute effects of psilocybin in healthy participants. The findings from this study will further our understanding of the impact of psychedelics on motor function, and inform future studies that combine classic psychedelics with motor retraining in clinical populations. Methods 12 healthy participants will each receive three doses of psilocybin (between 5 and 20 mg) in a randomized order, with each dose administered at least 1 week apart. Participants, the trial physiotherapists, and statisticians will remain blinded to the psilocybin dose. A battery of measures assessing motor function will be completed during the acute drug effects. In addition, measures of safety, pre‐ and post‐dose resting‐state brain activity via functional magnetic resonance imaging, and participants' subjective experience will be assessed.